Copper-manganese fiber-loaded molecular sieve film and its preparation method and application

The copper-manganese nanofiber membrane was prepared through electrospinning technology and loaded with molecular sieve, which solved the problem of inefficiency of traditional fixed bed adsorbers in VOCs treatment, achieved efficient purification of organic pollutants and improved catalyst stability, significantly improved VOCs degradation rate and economical environmental restoration.

CN116273138BActive Publication Date: 2024-12-17BEIJING NORMAL UNIV AT ZHUHAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310291998.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2024-12-17
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

When dealing with volatile organic compounds (VOCs), traditional fixed bed adsorbers have problems such as catalyst deactivation, low contact efficiency, large mass transfer heat transfer resistance and large bed pressure drop, and existing catalysts have low degradation efficiency for VOCs.

Method used

Electrospinning technology is used to prepare copper-manganese nanofiber membranes and load molecular sieves on its surface. The copper-manganese fiber-supported molecular sieve film is formed by secondary growth liquid crystallization, combining the synergistic effect of polymers and nanometals to improve the performance and adsorption of catalysts. ability.

Benefits of technology

It significantly improves the degradation rate of VOCs, achieves efficient purification of organic pollutants, reduces the cost and recyclability of catalysts, and improves the economic benefits of environmental pollution restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273138B_ABST
    Figure CN116273138B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of composite materials, and specifically relates to a copper-manganese fiber-loaded molecular sieve film and a preparation method and application thereof. The copper-manganese fiber-loaded molecular sieve film obtained by the present invention through electrostatic spinning and secondary growth method has a high surface area and high mechanical strength, and can efficiently catalyze and degrade organic pollutants by combining the adsorption and catalytic properties of molecular sieves and copper and manganese; at the same time, it can effectively exert the synergistic effect of nano-metal particles and molecular sieves, solve the problem of easy agglomeration of nano-metal particles, increase the dispersibility of nano-particles, and improve the catalytic oxidation activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a copper-manganese fiber-loaded molecular sieve film and a preparation method and application thereof. Background Art

[0002] With the vigorous development of modern industry and the continuous improvement of people's environmental awareness, environmental pollution has received more and more attention. Organic waste is an important source of environmental pollution. The emissions of volatile organic compounds (VOCs) generated by industries such as petrochemicals, chemicals and interior decoration are increasing. Their effective treatment and remediation of the polluted environment have become a research topic for many scholars.

[0003] Among various VOCs treatment methods, adsorption and catalytic combustion methods have the advantages of simple operation, low energy consumption and high purification efficiency, and are widely used in the field of removing VOCs from the air. However, traditional fixed bed adsorbers / reactors are generally filled with granular or powdered adsorbents / catalysts. For the selection of adsorbents, molecular sieve adsorbents have the advantages of non-flammability, high mechanical strength, strong hydrophobicity, good thermodynamic and chemical stability compared to activated carbon adsorbents. However, the pore size of zeolite molecular sieves is between 0.3 and 2 nm, and its adsorption and catalytic applications are limited to molecules with a molecular kinetic diameter of less than 2 nm. Due to the limitation of pore size, carbon deposition and pore plugging are easily generated during the catalytic process, leading to catalyst deactivation. Adsorption methods generally have the disadvantages of low contact efficiency, large mass transfer and heat transfer resistance, and large bed pressure drop.

[0004] Catalytic oxidation technology is to catalytically oxidize VOCs into CO2 and H2O under the action of a catalyst. The active components of the catalyst are usually loaded on a porous granular carrier with a high specific surface area (the catalyst carrier is usually a porous material with high thermodynamic stability and no catalytic activity), thereby improving the performance of the catalyst. Precious metals are expensive and easily deactivated at high temperatures. By selecting appropriate active components of transition metal oxide catalysts, transition metal oxide catalysts with low cost, high activity and stability can be obtained. However, the current catalysts all have the problem of low efficiency in degrading VOCs. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a copper-manganese fiber-loaded molecular sieve film and a preparation method and application thereof. The copper-manganese fiber-loaded molecular sieve film of the present invention has a high degradation rate for VOCs.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a copper-manganese fiber-loaded molecular sieve film, comprising the following steps:

[0008] Mixing a polymer, nano copper, nano manganese, n-octyltrimethylammonium bromide and N,N-dimethylformamide to obtain a spinning solution; the polymer includes polyacrylonitrile or polystyrene;

[0009] Electrospinning the spinning solution to obtain a copper-manganese nanofiber membrane;

[0010] calcining the copper-manganese nanofiber membrane to obtain a calcined film;

[0011] After soaking the calcined film in a cationic polymer solution, washing and drying are performed in sequence to obtain a positively charged film;

[0012] After immersing the positively charged film in a silicalite-1 seed solution, washing and drying are performed in sequence to obtain a film with seed crystals;

[0013] After the film with seed crystals is liquid crystallized with the secondary growth, washing, drying and second calcination are carried out in sequence to obtain the copper-manganese fiber-loaded molecular sieve film; the secondary growth liquid is obtained by pre-crystallization of a raw material liquid, and the raw material liquid includes silicon dioxide, a template agent and water.

[0014] Preferably, the molar ratio of the nano-copper to the nano-manganese is 1:0.5-8.

[0015] Preferably, the concentration of the polymer in the spinning solution is 50 to 300 g / L.

[0016] Preferably, the mass ratio of the polymer to the metal is 3:1-2, and the metal includes nano-copper and nano-manganese.

[0017] Preferably, the temperature of the first calcination is 500-600° C., and the time is 4-8 hours.

[0018] Preferably, the second calcination is performed at a temperature of 400 to 600° C. and for a time of 2 to 6 hours.

[0019] Preferably, the pre-crystallization temperature is 100-200° C. and the time is 12-36 hours.

[0020] Preferably, the silicalite-1 seed solution is obtained by crystallizing a mixture of tetrapropylammonium hydroxide, water and ethanol at 50 to 150° C. for 12 to 36 hours.

[0021] The present invention also provides a copper-manganese fiber-loaded molecular sieve film obtained by the preparation method described in the above technical solution, comprising a molecular sieve and a copper-manganese fiber membrane, wherein the molecular sieve is loaded on the surface of the copper-manganese fiber membrane.

[0022] The present invention also provides application of the copper-manganese fiber-loaded molecular sieve film in the field of degrading organic pollutants.

[0023] The present invention provides a method for preparing a copper-manganese fiber-loaded molecular sieve film, comprising the following steps:

[0024] Mixing a polymer, nano copper, nano manganese, n-octyltrimethylammonium bromide and N,N-dimethylformamide to obtain a spinning solution; the polymer includes polyacrylonitrile or polystyrene;

[0025] Electrospinning the spinning solution to obtain a copper-manganese nanofiber membrane;

[0026] calcining the copper-manganese nanofiber membrane to obtain a calcined film;

[0027] After soaking the calcined film in a cationic polymer solution, washing and drying are performed in sequence to obtain a positively charged film;

[0028] After immersing the positively charged film in a silicalite-1 seed solution, washing and drying are performed in sequence to obtain a film with seed crystals;

[0029] After the film with seed crystals is liquid crystallized with the secondary growth, washing, drying and second calcination are carried out in sequence to obtain the copper-manganese fiber-loaded molecular sieve film; the secondary growth liquid is obtained by pre-crystallization of a raw material liquid, and the raw material liquid includes silicon dioxide, a template agent and water.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention has developed a novel method for preparing a copper-manganese fiber-loaded molecular sieve film material. The electrostatic spinning technology is used to prepare nano-copper and nano-manganese into a copper-manganese nanofiber membrane with a high specific area and high porosity, and then the molecular sieve is loaded on the surface of the copper-manganese fiber membrane. The molecular sieve can not only give play to the characteristics of the molecular sieve being porous and having good adsorption performance, but also give play to the advantages of the copper-manganese fiber membrane having high catalytic efficiency, and has a high degradation rate for VOCs. The present invention has very important practical significance for achieving efficient and green purification of organic waste, improving the economic benefits of environmental pollution remediation, and achieving sustainable development.

[0032] The copper-manganese fiber-loaded molecular sieve film material prepared by the present invention makes nano-copper and nano-manganese into a copper-manganese fiber membrane. Compared with simple copper-manganese composite metal oxides as catalysts, the copper-manganese fiber membrane has the advantages of easy recovery and good dispersibility. Compared with directly loading copper and manganese on the molecular sieve, the copper-manganese fiber membrane can load more copper and manganese oxides, which can effectively improve the catalytic effect.

[0033] At the same time, the present invention combines polymers (polyacrylonitrile, polystyrene) with catalyst precursors (nano copper, nano manganese), utilizes the advantages of high porosity and high permeability of organic nanofibers, effectively exerts the synergistic effect of nano copper, nano manganese and polymer material carriers, solves the problem of easy agglomeration of nano copper and nano manganese, gives full play to their catalytic performance, and reduces the leaching of nano particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 This is the microscopic morphology of the copper-manganese fiber-loaded molecular sieve film of Example 1. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a copper-manganese fiber-loaded molecular sieve film, comprising the following steps:

[0037] Mixing a polymer, nano copper, nano manganese, n-octyltrimethylammonium bromide and N,N-dimethylformamide to obtain a spinning solution; the polymer includes polyacrylonitrile or polystyrene;

[0038] Electrospinning the spinning solution to obtain a copper-manganese nanofiber membrane;

[0039] The copper-manganese nanofiber membrane is subjected to a first calcination to obtain a calcined film;

[0040] After soaking the calcined film in a cationic polymer solution, washing and drying are performed in sequence to obtain a positively charged film;

[0041] After soaking the positively charged film in silicalite-1 seed solution, washing and drying are performed in sequence to obtain a film with seed crystals;

[0042] After the film with seed crystals is liquid crystallized with the secondary growth, washing, drying and second calcination are carried out in sequence to obtain the copper-manganese fiber-loaded molecular sieve film; the secondary growth liquid is obtained by pre-crystallization of a raw material liquid, and the raw material liquid includes silicon dioxide, a template agent and water.

[0043] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.

[0044] The invention mixes high polymer, nano copper, nano manganese, n-octyltrimethylammonium bromide and N,N-dimethylformamide to obtain a spinning solution; the high polymer includes polyacrylonitrile or polystyrene.

[0045] The present invention preferably performs a first mixing of a polymer and N,N-dimethylformamide to obtain a polymer solution, and then performs a second mixing of the polymer solution, nano-copper, nano-manganese and n-octyltrimethylammonium bromide to obtain the spinning solution; the first mixing and the second mixing are preferably performed by stirring with a magnetic stirrer, and the present invention has no special requirements for the time of the first mixing, as long as the polymer is dissolved in N,N-dimethylformamide, and the N,N-dimethylformamide is a solvent; the second mixing time is preferably 1 to 3 hours.

[0046] In the present invention, the concentration of the polymer in the spinning solution is preferably 50 to 300 g / L, more preferably 100 g / L.

[0047] In the present invention, the particle sizes of the nano-copper and nano-manganese are preferably both 100 nm.

[0048] In the present invention, the molar ratio of the nano-copper to the nano-manganese is preferably 1:0.5-8, more preferably 1:1-6, and even more preferably 1:3.

[0049] In the present invention, the mass ratio of the polymer to the metal is preferably 3:1-2, more preferably 2:0.7. The metal includes nano copper and nano manganese, and the mass of the metal is preferably 10-40% of the mass of the polymer.

[0050] In the present invention, the concentration of n-octyltrimethylammonium bromide in the spinning solution is preferably 1-9 mmol / L, more preferably 7-9 mmol / L, and even more preferably 8.3 mmol / L; the n-octyltrimethylammonium bromide can evenly disperse the nano-copper and nano-manganese particles.

[0051] After obtaining the spinning solution, the present invention performs electrostatic spinning on the spinning solution to obtain the copper-manganese nanofiber membrane.

[0052] In the present invention, the parameters of the electrospinning include: the positive voltage is preferably +5 to 20 kV, more preferably +15 kV, the negative voltage is preferably -0 to 5 kV, more preferably -2 kV; the distance from the receiver to the needle is preferably 2 to 8 cm, more preferably 4.5 cm; the electrospinning time is preferably 20 to 60 min, more preferably 40 min.

[0053] After obtaining the copper-manganese nanofiber membrane, the present invention performs a first calcination on the copper-manganese nanofiber membrane to obtain a calcined film.

[0054] In the present invention, the temperature of the first calcination is preferably 500-600°C, more preferably 550°C; the time is preferably 4-8h, more preferably 6h; the first calcination can shape the copper-manganese nanofiber membrane and form a porous oxide film on the surface of the copper-manganese nanofiber membrane.

[0055] In the present invention, the first calcination is preferably carried out in an air atmosphere. In a specific embodiment of the present invention, the first calcination is carried out in a muffle furnace.

[0056] After obtaining the calcined film, the present invention soaks the calcined film in a cationic polymer solution, and then washes and dries the film in sequence to obtain a positively charged film.

[0057] In the present invention, the cationic polymer solution is preferably a polyhydroxypropyl dimethyl ammonium chloride aqueous solution, and the concentration of the polyhydroxypropyl dimethyl ammonium chloride aqueous solution is preferably 0.25-0.75wt%, more preferably 0.5wt%. The present invention has no special requirements on the amount of the polyhydroxypropyl dimethyl ammonium chloride aqueous solution, and it is sufficient to immerse the calcined film. Immersing the calcined film in the cationic polymer solution can make the obtained film positively charged.

[0058] In the present invention, the soaking time is preferably 20 to 40 minutes, more preferably 30 minutes.

[0059] In the present invention, the washing reagent is preferably ammonia water, and the concentration of the ammonia water is preferably 0.05-0.25 mol / L, more preferably 0.1 mol / L. The use of ammonia water for washing can keep the film positively charged.

[0060] In the present invention, the drying method is preferably air-drying at room temperature.

[0061] After obtaining the positively charged film, the present invention soaks the positively charged film in silicalite-1 seed solution, and then washes and dries the film in sequence to obtain a film with seed crystals.

[0062] In the present invention, the silicalite-1 seed solution is preferably obtained by crystallizing a mixture of tetrapropylammonium hydroxide, water and ethanol at 50-150° C. for 12-36 hours; the crystallization temperature is more preferably 100° C., and the crystallization time is more preferably 24 hours.

[0063] In the present invention, the mixture of tetrapropylammonium hydroxide, water and ethanol preferably further contains tetraethoxysilane, and the molar ratio of tetraethoxysilane (TEOS), tetrapropylammonium hydroxide (TPAOH), water and ethanol is preferably 0-1.5:0.36:20:4, and the molar number of tetraethoxysilane is not 0, and is more preferably 1:0.36:20:4.

[0064] In the present invention, the soaking time is preferably 12 to 36 hours, more preferably 24 hours; the soaking can enable the positively charged film to adsorb the seed crystals.

[0065] In the present invention, the washing reagent is preferably ammonia water, and the concentration of the ammonia water is preferably 0.05-0.25 mol / L, more preferably 0.1 mol / L. The use of ammonia water for washing can keep the film positively charged.

[0066] In the present invention, the drying temperature is preferably 105° C. and the drying time is preferably 12 h.

[0067] After obtaining the film with seed crystals, the present invention liquid crystallizes the film with seed crystals and the secondary growth, and then washes, dries and performs a second calcination in sequence to obtain the copper-manganese fiber-loaded molecular sieve film; the secondary growth liquid is obtained by pre-crystallization of the raw material liquid, and the raw material liquid includes silicon dioxide, a template agent and water.

[0068] In the present invention, the pre-crystallization temperature is preferably 100-200° C., more preferably 175° C.; the pre-crystallization time is preferably 12-36 h, more preferably 24 h.

[0069] In the present invention, the template is preferably tetrapropylammonium hydroxide (TPAOH).

[0070] In the present invention, the raw material solution preferably further contains alumina, and the molar ratio of alumina, silica, template and water is preferably 0 to 0.118:1:0.112:111, and the molar number of alumina is not 0, and is more preferably 0.118:1:0.112:111.

[0071] In the present invention, the crystallization temperature is preferably 50-150°C, more preferably 100°C; the time is preferably 12-36h, more preferably 24h. In a specific embodiment of the present invention, the film with seed is vertically placed in a stainless steel reactor filled with secondary growth liquid and lined with polytetrafluoroethylene for crystallization, and the molecular sieve is secondary grown.

[0072] In the present invention, the washing agent is preferably deionized water.

[0073] In the present invention, the drying temperature is preferably 50 to 150°C, more preferably 100°C.

[0074] In the present invention, the temperature of the second calcination is preferably 400-600° C., more preferably 500° C., and the time is preferably 2-6 hours, more preferably 4 hours; the second calcination can shape the film and remove the template at the same time.

[0075] In the present invention, the heating rate from room temperature to the temperature of the second calcination is preferably 1-3° C. / min.

[0076] In the present invention, the second calcination preferably further includes cooling to room temperature, and the cooling rate from the temperature of the second calcination to room temperature is preferably 1-3°C / min.

[0077] The present invention also provides a copper-manganese fiber-loaded molecular sieve film obtained by the preparation method described in the above technical solution, comprising a molecular sieve and a copper-manganese fiber membrane, wherein the molecular sieve is loaded on the surface of the copper-manganese fiber membrane.

[0078] In the present invention, the specific surface area of ​​the copper-manganese fiber-loaded molecular sieve film is preferably 100 to 300 m 2 / g.

[0079] In the present invention, the copper and manganese in the copper-manganese fiber-loaded molecular sieve film exist in the form of oxide fibers.

[0080] The present invention also provides application of the copper-manganese fiber-loaded molecular sieve film in the field of degrading organic pollutants.

[0081] In the present invention, the organic pollutant preferably includes isopropanol, and the isopropanol is preferably degraded in a fixed bed reactor. The isopropanol is in a gaseous state when degraded in the fixed bed reactor.

[0082] In the present invention, the degradation parameters preferably include: temperature of 210°C, air velocity of 3822h -1 , the inlet concentration of isopropanol was 4.7 mg / L, and the bed height was 2 cm.

[0083] The present invention utilizes electrostatic spinning technology to prepare copper-manganese metal fiber membrane, which can improve the dispersibility of metal particles and improve catalytic performance. At the same time, the secondary growth molecular sieve has good adsorption performance, and the pollutants can be first adsorbed around the catalytic membrane (copper-manganese fiber loaded molecular sieve film), thereby improving the contact area and contact efficiency between the catalytic membrane and the pollutants. The present invention can effectively exert the synergistic effect of copper-manganese nanofibers and molecular sieves, solve the problem that nano-metal particles are easy to agglomerate and the carrier is difficult to regenerate, give full play to its catalytic and adsorption performance, and can efficiently catalytically degrade organic pollutants. The copper-manganese fiber loaded molecular sieve film of the present invention has a degradation rate of 95-99% for isopropanol.

[0084] In order to further illustrate the present invention, the copper-manganese fiber-loaded molecular sieve film and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0085] Example 1

[0086] A method for preparing a copper-manganese fiber-loaded molecular sieve film comprises the following steps:

[0087] 1. Preparation of 100 g / L polyacrylonitrile solution: Weigh 2 g of polyacrylonitrile solid, dissolve it in 20 mL of N,N-dimethylformamide, put in a magnetic bar, and stir on a magnetic stirrer;

[0088] 2. Preparation of copper-manganese nanofiber membrane:

[0089] 1) Weigh 0.114 g of 100 nm nano copper, 0.586 g of 100 nm nano manganese, and 0.0419 g of n-octyltrimethylammonium bromide and dissolve them in the 100 g / L polyacrylonitrile solution obtained in step 1, and stir on a magnetic stirrer for 3 h to obtain a spinning solution;

[0090] 2) Use a syringe to extract 2 mL of the spinning solution, adjust the distance from the needle to the receiver to 4.5 cm, and the voltage of the electrospinning machine to +15 kV and -2 kV. After the receiver is stable, start spinning for 40 minutes;

[0091] 3. Preparation of copper-manganese fiber loaded molecular sieve film:

[0092] 1) The copper-manganese nanofiber membrane obtained by spinning is quickly placed in a muffle furnace and calcined at 550° C. for 6 h in an air atmosphere to form a porous oxide film on the fiber surface;

[0093] 2) soaking the film with a porous oxide film in a 0.5 wt % polyhydroxypropyl dimethyl ammonium chloride cationic polymer solution for 30 min, washing it three times with 0.1 mol / L ammonia water, and drying it at room temperature to obtain a positively charged film;

[0094] 3) preparing a silicalite-1 seed solution according to a synthesis formula of TEOS, TPAOH, H2O and EtOH in a molar ratio of 1:0.36:20:4 by crystallization at 100°C for 24 hours, soaking the dried positively charged film in the silicalite-1 seed solution for 24 hours, washing the film with 0.1 mol / L ammonia water, and drying for standby use to obtain a film with seeds;

[0095] 4) crystallizing at 175° C. for 24 h to obtain a secondary growth solution according to a synthesis formula in which the molar ratio of SiO2, TPAOH, Al2O3 and H2O is 1:0.112:0.118:111, and vertically placing the obtained film with seed into a stainless steel reactor lined with polytetrafluoroethylene containing the secondary growth solution, and crystallizing at 100° C. for 24 h;

[0096] 5) After the reactor is taken out, it is quickly cooled with cold water, the membrane is rinsed with deionized water, dried at 100°C, heated to 500°C at a rate of 1°C / min in a muffle furnace, kept warm and calcined for 4 hours, and then cooled to room temperature at the same rate to remove the template to obtain a copper-manganese fiber-loaded molecular sieve film.

[0097] Performance Testing:

[0098] Figure 1 This is a microscopic morphology of the copper-manganese fiber-loaded molecular sieve film obtained in Example 1.

[0099] The specific surface area of ​​the copper-manganese fiber-loaded molecular sieve film obtained in Example 1 is 163 m 2 / g, and the porosity is 87%.

[0100] The copper-manganese fiber-supported molecular sieve film prepared in Example 1 was subjected to a catalytic performance test experiment. Isopropanol was used as the target pollutant at a temperature of 210°C and a space velocity of 3822 h -1 Under the experimental conditions of isopropanol inlet concentration of 4.7 mg / L and bed height of 2 cm, the isopropanol conversion rate was 98%.

[0101] Example 2

[0102] The only difference between this embodiment and embodiment 1 is that: 0.196g of 100nm nano-copper and 0.504g of 100nm nano-manganese are weighed, and the other steps are the same as those in embodiment 1.

[0103] Performance Testing:

[0104] The specific surface area of ​​the copper-manganese fiber-loaded molecular sieve film obtained in Example 2 is 150 m 2 / g, and the porosity is 85%.

[0105] The copper-manganese fiber-supported molecular sieve film prepared in Example 2 was subjected to a catalytic performance test experiment under the same experimental conditions as in Example 1, and the isopropanol conversion rate was 99%.

[0106] Example 3

[0107] The only difference between this embodiment and embodiment 1 is that: 0.376g of 100nm nano-copper and 0.324g of 100nm nano-manganese are weighed, and the other steps are the same as those in embodiment 1.

[0108] Performance Testing:

[0109] The specific surface area of ​​the copper-manganese fiber-loaded molecular sieve film obtained in Example 3 is 157 m 2 / g, and the porosity is 85%.

[0110] The copper-manganese fiber-supported molecular sieve film prepared in Example 3 was subjected to a catalytic performance test experiment. The experimental conditions were the same as those in Example 1, and the isopropanol conversion rate was 95%.

[0111] Comparative Example 1

[0112] (1) Weigh 2 g of polyacrylonitrile solid, dissolve it in 20 mL of N,N-dimethylformamide, add a magnetic bar, and stir on a magnetic stirrer for 3 h;

[0113] (2) Using a syringe to extract 2 mL of the solution obtained in step (1), adjusting the distance from the needle to the receiver to 4.5 cm, the voltage of the electrospinning machine to +15 kV and -2 kV, and starting spinning for 40 min after the receiver is stable;

[0114] (3) The membrane obtained by spinning is quickly placed in a muffle furnace and calcined at 550° C. for 6 h in an air atmosphere to form a porous oxide film on the fiber surface;

[0115] (4) Weigh 0.376 g of 100 nm nano-copper and 0.324 g of 100 nm nano-manganese and dissolve them in 100 mL of water, and immerse the membrane obtained in step (3) in the solution for 1 hour;

[0116] (5) Drying at 100 °C, heating to 500 °C at a rate of 1 °C / min in a muffle furnace, calcining at this temperature for 4 h, and then cooling to room temperature at the same rate to obtain a fiber-loaded copper-manganese film.

[0117] Performance Testing:

[0118] The specific surface area of ​​the fiber-loaded copper-manganese film obtained in Comparative Example 1 is 15 m 2 / g, and the porosity is 90%.

[0119] The fiber-supported copper-manganese film prepared in Comparative Example 1 was subjected to a catalytic performance test experiment. The experimental conditions were the same as those in Example 1, and the isopropanol conversion rate was 68%.

[0120] Comparative Example 2

[0121] (1) Weigh 2 g of polyacrylonitrile solid, dissolve it in 20 mL of N,N-dimethylformamide, add a magnetic bar, and stir on a magnetic stirrer for 3 h;

[0122] (2) Using a syringe to extract 2 mL of the solution obtained in step (1), adjusting the distance from the needle to the receiver to 4.5 cm, the voltage of the electrospinning machine to +15 kV and -2 kV, and starting spinning for 40 min after the receiver is stable;

[0123] (3) The membrane obtained by spinning is quickly placed in a muffle furnace and calcined at 550° C. for 6 h in an air atmosphere to form a porous oxide film on the fiber surface;

[0124] (4) soaking the membrane obtained in step (3) in a 0.5 wt % polyhydroxypropyl dimethyl ammonium chloride cationic polymer solution for 30 min, washing it three times with 0.1 mol / L ammonia water, and drying it at room temperature;

[0125] (5) preparing a silicalite-1 seed solution by crystallizing at 100° C. for 24 h according to a synthetic formula of TEOS, TPAOH, H2O and EtOH in a molar ratio of 1:0.36:20:4, soaking the film dried in step (4) in the silicalite-1 seed solution for 24 h, washing the film with 0.1 mol / L ammonia water, and drying for later use;

[0126] (6) crystallizing at 175° C. for 24 h to obtain a secondary growth solution according to a synthesis formula in which the molar ratio of SiO2, TPAOH, Al2O3 and H2O is 1:0.112:0.118:111, and the film obtained in step (5) is vertically placed in a stainless steel reactor filled with the secondary growth solution and lined with polytetrafluoroethylene and crystallized at 100° C. for 24 h;

[0127] (7) After the reactor is taken out, it is quickly cooled with cold water, the membrane is rinsed with deionized water, dried at 100°C, heated to 500°C at a rate of 1°C / min in a muffle furnace, kept for calcination for 4 hours, and then cooled to room temperature at the same rate to remove the organic template to obtain a fiber-loaded molecular sieve film.

[0128] Performance Testing:

[0129] The specific surface area of ​​the fiber-supported molecular sieve membrane obtained in Comparative Example 2 is 148 m 2 / g, and the porosity is 87%.

[0130] The fiber-supported molecular sieve film prepared in Comparative Example 2 was subjected to a catalytic performance test experiment. The experimental conditions were the same as those in Example 1, and the isopropanol conversion rate was 35%.

[0131] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a copper-manganese fiber-loaded molecular sieve film, characterized in that: The following steps are involved: Mixing a polymer, nano copper, nano manganese, n-octyltrimethylammonium bromide and N,N-dimethylformamide to obtain a spinning solution; the polymer includes polyacrylonitrile or polystyrene; the molar ratio of the nano copper to the nano manganese is 1:0.5-8; Electrospinning the spinning solution to obtain a copper-manganese nanofiber membrane; The copper-manganese nanofiber membrane is subjected to a first calcination to obtain a calcined film; After soaking the calcined film in a cationic polymer solution, washing and drying are performed in sequence to obtain a positively charged film; After soaking the positively charged film in silicalite-1 seed solution, washing and drying are performed in sequence to obtain a film with seed crystals; After the film with seed crystals is liquid crystallized with the secondary growth, washing, drying and second calcination are carried out in sequence to obtain the copper-manganese fiber-loaded molecular sieve film; the secondary growth liquid is obtained by pre-crystallization of a raw material liquid, and the raw material liquid includes silicon dioxide, a template agent and water.

2. The preparation method according to claim 1, characterized in that: The concentration of the polymer in the spinning solution is 50-300 g / L.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the polymer to the metal is 3:1-2, and the metal includes nano copper and nano manganese.

4. The preparation method according to claim 1, characterized in that: The first calcination is carried out at a temperature of 500-600° C. and for a time of 4-8 hours.

5. The preparation method according to claim 1, characterized in that: The second calcination is carried out at a temperature of 400-600° C. and for a time of 2-6 hours.

6. The preparation method according to claim 1, characterized in that: The pre-crystallization temperature is 100-200° C. and the time is 12-36 hours.

7. The preparation method according to claim 1, characterized in that: The silicalite-1 seed solution is obtained by crystallizing a mixture of tetrapropylammonium hydroxide, tetraethoxysilane, water and ethanol at 50-150° C. for 12-36 hours.

8. The copper-manganese fiber-loaded molecular sieve film obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises a molecular sieve and a copper-manganese fiber membrane, wherein the molecular sieve is loaded on the surface of the copper-manganese fiber membrane.

9. Use of the copper-manganese fiber-loaded molecular sieve membrane according to claim 8 in the field of degradation of volatile organic compounds.